Exploring EFL Students’ Perception on the Use of Artificial Intelligence (AI) in Enhancing English Language Skills - Mulyana, Novita; Novi Utami, Gek Wulan; Neil Prajamukti Wardhana, I Gede (Universitas Jambi, Magister Program of English Education Department, 2026)
The rapid development of artificial intelligence (AI) is undeniable, including in learning English as a foreign language. However, the use of AI, in English language learning is still quite controversial. Its use sparks pros and cons among researchers and language instructors. This research is a mixed-method case study adopting the Technology Acceptance Model (TAM) that aimed at exploring undergraduate students’ perception on the use of AI tools to enhance their English skills. The data of this study were collected in two stages: (1) by using a questionnaire (n=149) and (2) by conducting semi-structured interviews (n=36). The collected data were analysed using a convergent parallel design. The result of the study shows that the participants are familiar with 21 different AI tools, with ChatGPT as the most frequently used AI tool. It is also shown that there is high degree of Perceived Usefulness (PU) and Perceived Ease of Use (PEoU) from the participants towards the use of AI. However, the participants also expressed significant concerns regarding over-reliance and the potential erosion of critical thinking due to the use of AI. As the result, despite the high degree of PU and PEoU, the students prefer to use AI to support their individual learning activities, rather than relying on it to replace classroom instructions. The results of this study provide a deeper understanding of the psychological drivers underlying AI acceptance and offers specific pedagogical recommendations, such as the integration of AI literacy into the EFL syllabus.